Status Teknologi Semasa Dalam PKS Pembuatan Bumiputera di Negeri Kedah - Mazri, Yaakob (2010)
This study describe four technology component mutually related namely Technoware, Humanware, Infoware and Orgaware which respectively having their distinctive elements. As many as 51 SMEs' owners or entrepreneur in Kedah were selected as respondent. SME is chosen as SME is GDP major contributor. The information of SME in Kedah achieved through directory of SME CORP Malaysia, FMM and PKNK. Interview method by face to face and questionnaire distribution through post were used to seek the data. However, data derivative through interview by face to face were more numerous compared through post. This study used tricky technology component weight measurement of Saaty method which is known as AHP as the indicator of SME current technology's status in Kedah. The result of analysis indicated that micro scales SME inclined micro on Orgaware component, while small scale SME emphasize Technoware component. Medium scale SME also show equivalent technology component involvement. Overall, SMEs shows tendency on Orgaware component and are followed by Technoware, Humanware and Infoware.